New Aryloxy-Quinone Derivatives as Potential Anti-Chagasic Agents: Synthesis, Trypanosomicidal Activity, Electrochemical Properties, Pharmacophore Elucidation and 3d-Qsar Analysis - Segura-Segura, R; Segura-Segura, R; Pizarro-Reyes, J; Pizarro-Reyes, J (Royal Society of Chemistry, 2015)
A set of new aryloxy-quinones were synthesized and evaluated in vitro against the epimastigote form of Trypanosoma cruzi and their unspecific cytotoxicity was tested on murine macrophages J-774 cells. Most of these novel compounds were found to be much more potent and selective than the standard drug nifurtimox. Interestingly, 2-phenoxy-naphthoquinone 3b displayed a remarkable nanomolar inhibitory activity, IC50 = 20 nM, and a high selectivity index, SI = 625. The Epc1 was determined for the most interesting compounds and no correlation with the trypanosomicidal effect was found. Therefore, an in silico study was carried out to obtain a pharmacophoric model and quantitative structure-trypanosomicidal activity relationship. The designed pharmacophore recognized the more potent and selective molecules, exhibiting five pharmacophoric features. A correlation coefficient R2 of 0.99 of pIC50 plotted against the predicted values indicated that the 3D-QSAR equation could be applied to further predictions of newly designed trypanosomicidal compounds. © 2015 Royal Society of Chemistry.